Perlindungan Hukum Terhadap Nasabah Laku Pandai Atas Kerugian Akibat Perbuatan Agen Brilink - Agnes Cynthia; Ayu Safa Mutiara; Reta Indah Kusmaputri; Dwi Desi Yayi Tarina (Journal of Indonesian Comparative of Syari'ah Law, 2023)
Laku Pandai is a financial service created by the organizing bank to make it easier for people who use banks to reach banks to carry out other financial interests. This is based on the Financial Services Authority Regulation (POJK) Number 19 / POJK. 03 / 2014 concerning Office-less Financial Services in the Framework of Inclusive Finance. With this regulation, Bank BRI opened Laku Pandai services under the name BRILink, but as the implementation of Laku Pandai organized by BRILink progresses, many unscrupulous BRILink Agents take advantage of opportunities that ultimately harm customers in financial terms. This article explains the legal protection of losses suffered by Laku Pandai customers and the legal responsibility of BRILink Agents who commit criminal acts of embezzlement of BRILink customer money with normative juridical research methods. This article is made with the aim that the organizing Bank must provide special protection for Laku Pandai user customers and strive to supervise the activities of Laku Pandai Agents firmly so that criminal acts that harm customers do not occur.